Precision micro-machining of silicon and glass - Venkatesh, V. C. (2002)
This research work is concentrated on machining of flat surfaces on silicon and glass for applications like IC chips and small optical lenses. Aspheric surfaces were also generated on silicon and germanium. Grinding was done to give a good surface finish and at the same time focused on getting the maximum amount of ductile streaks. After grinding the surfaces were lapped and polished. The polishing curve is a saturation curve where rapid improvement in surface finish is obtained followed by a gradual decrease in the Ra, with the curve flattening out parallel to the horizontal time axis. It was found that the initial roughness after grinding was not the sole criterion for rapid polishing but rather the amount of ductile streaks. The amount of ductile streaks is not only dependant on the feed and the depth of cut but also on the grit size of the diamonds as well as its concentration, and not least of all on the type of bond. Brightness of silicon surfaces and lightness of glass workpieces and their relationship with roughness have been determined.